Senex sapiens et senex stupidus – wykorzystanie figury starca w alegorycznych kreacjach Sędziego, Lichwy i Alchemii w podręczniku Franza Langa SI „De actione scenica”, 1727 - Zaborowska-Musiał, Justyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The article focuses on the analysis of the role and importance of the figure of an old man in the allegorical images of Judge (Iudex), Usury (Foeneratio) and Alchemy (Alchimia) proposed by the Jesuit lecturer, playwright, and author of theatrical performances and drama theatre theorist, Franz Lang in his very important (it marked an high point of theatrical outpoot) handbook of acting De actione scenica published in Munich in 1727.